2015
DOI: 10.1111/jnu.12121
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Community Participation in the CDTI Program in Morogoro, Tanzania

Abstract: Background: Up to 4 million people in Tanzania are at risk for the parasitic disease onchocerciasis. A treatment program, Community-Directed Treatment with Ivermectin (CDTI), has made significant gains in prevention and treatment. Understanding factors affecting participation could help boost treatment coverage and sustain gains made in controlling onchocerciasis in endemic areas. Purpose: To explore community-perceived factors related to participation in and sustainability of the CDTI program in southwest Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Insufficiently trained drug distributors were likely to jeopardize uptake as their lack of knowledge endangered recipients' trust in the intervention. These findings are corroborated by studies on MDA for LF and onchocerciasis in Tanzania, where poor training was linked by respondents to limited ability to allay community members' concerns on drug safety [21,24]. With the exception of ensuring sufficient time is given towards training, previous studies have highlighted the importance of training without providing further detail on what factors contribute towards effective training [17,21].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 76%
“…Insufficiently trained drug distributors were likely to jeopardize uptake as their lack of knowledge endangered recipients' trust in the intervention. These findings are corroborated by studies on MDA for LF and onchocerciasis in Tanzania, where poor training was linked by respondents to limited ability to allay community members' concerns on drug safety [21,24]. With the exception of ensuring sufficient time is given towards training, previous studies have highlighted the importance of training without providing further detail on what factors contribute towards effective training [17,21].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 76%
“…Educating community members empowers communities and serves to increase participation in the desired health activity. As York et al [ 21 ] concluded when analyzing onchocerciasis control programs in Tanzania, programs’ success and sustainability is largely predicated on community sensitization.…”
Section: Primary Prevention Activitiesmentioning
confidence: 99%
“…CDDs in Ulanga have a role in educating, motivating and ensuring that community members participate in the control of onchocerciasis by visiting households before ivermectin distribution to sensitize the community. Clearly, some of the challenges mentioned by CDDs in the implementation of the CDTI programme in Ulanga, such as hard-to-reach hamlets, doubt about the method of dose calculation and fear of side effects, were also revealed by another study performed in Tanzania by (12).…”
Section: Discussionmentioning
confidence: 97%